The Effect of “Harry Potter and the Chamber of The Secret” Movie Towards Listening Skill At SMAN 1 Bangkinang Kota: An Experimental Research at Eleventh Grade of SMAN 1 Bangkinang Kota - Nona Alanis Fauziah Haris; Masrul Masrul (Journal of Innovative and Creativity, 2025)
This research was motivated by the low listening skills observed among students at school. This experimental study was conducted in class XI of SMAN 1 Bangkinang Kota, aim of determining the effect of films on students' listening skills. The research employed a quasi-experimental design, with a sample of 72 students, consisting of 36 students from class X12 and 36 students from class XI.4. Data collection techniques included tests and documentation, with the data analyzed using SPSS version 26. Based on the research findings, it can be concluded that films can improve the listening skills of students in class XI.2, particularly on fantasy material. This improvement is reflected in the post-test average score of 84.42. Furthermore, the results of the Paired T-Test at: a 5% significance level showed Sig. (2-tailed)0.000, which is less than (0.025), indicating a statistically significant improvement.